Taken to health care provider or not, under-five children die of preventable causes: Findings from cross-sectional survey and social autopsy in Rural India - Vaishali Deshmukh; Chandrakant Lahariya; Sriram Krishnamurthy; Manoj K Das; Ravindra M Pandey; Narendra K Arora (Wolters Kluwer Medknow Publications, 2016)
Background: Under-five children in India continue to die from causes that can either be treated or prevented. The data regarding causes of death, community care-seeking practices, and events prior to death are needed to guide and refine health policies for achieving national goals and targets. Materials and Methods: A cross-sectional survey covering rural areas of 16 districts from eight states across India was conducted to understand the causes of deaths and the health-seeking patterns of caregivers prior to the death of such children. Mothers of the deceased children were interviewed. The physician review process was used to assign cause of death. The qualitative data were analyzed as per standard methods, while STATA version 10 was used for analysis of quantitative data. Findings: A total of 1,488 death histories were captured through verbal autopsy. Neonatal etiologies, acute respiratory infection (ARI), and diarrhea accounted for approximately 63.1% of all deaths in the under-five age group. The causes of death in neonates showed that birth asphyxia, prematurity, and neonatal infections contributed to more than 67.5% of all neonatal deaths, while in children aged 29 days to 59 months, ARI and diarrhea accounted for 54.3% of deaths. Care providers of 52.6% of the neonates and 21.7% of infants and under-five children did not seek any medical care before the death of the child. Substantial delays in seeking care occurred at home and during transit. For those who received medical care, there was an apparent amongst in their caregivers toward private health providers. Conclusion: The deaths of neonates and postneonates taken to any health facilities highlight the need for providing equitable and high-quality health services in India. The findings could be used for policy planning and program refinement in India.